Using a Modified Langmuir Equation to Estimate the Influence of Organic Materials on Phosphorus Adsorption in a Mollisol From Northeast, China - Wang, Zini; Hou, Liyuan; Liu, Zhenjuan; Cao, Ning; Wang, Xiaoli (Frontiers in Environmental Science, 2022)
The use of organic materials has been increasing due to improving soil fertility by affecting phosphorus (P) adsorption and desorption behavior of soils. However, previous studies ignored the influences of increased P concentrations in equilibrium solutions caused by P released from applied organic materials in bath P adsorption experiments. To eliminate these influences, a modified Langmuir equation was applied to describe P adsorption properties in dairy manure composts and biosolids-incubated soils. The adsorption and desorption trends shifted around the initial P concentration of 70 mg/L. The fitted parameter of correlation coefficients showed that the modified Langmuir model fitted well for the adsorption data covering only the lower initial P concentrations (0–70 mg P/L) and covering the whole P concentrations applied in the present study (0–400 mg/L). For the fitted results covering the whole P concentrations, adding organic materials generally decreased both the Γmax (maximum adsorption capacity for P) and the MABC (maximum adsorption buffering capacity), except for the 20-g/kg biosolids incubation, indicating that the number of adsorption sites for P decreased as the organic materials applied, and the binding energy for the P adsorption to the soil also decreased to some extent with some fluctuation as reflected by K values which represent adsorption strength. Higher DOC content, lower molecular weight, and higher humic acid might result in the higher Γmax of 20-g/kg biosolids incubated soil. The linear equations are described well for P desorption. The constant a value of slope in a linear equation reflects the P desorption capacity of soils increased due to the application of organic materials, especially in high P concentrations with a value of 0.45 for the control soil increased to 1.02 for 10-g/kg biosolids treated soil. Thus, it would be important to control the P application amounts when the application of P fertilizers to the soils with organic materials applied, as the effects of organic materials on P adsorption and desorption characteristics were more efficient at high P concentrations.